CONSEQUENCES OF FETAL GROWTH RESTRICTION DUE TO MATERNAL HIGH-RISK FACTORS ON NEONATAL OUTCOME WITH 1-YEAR FOLLOW-UP IN A TERTIARY CARE HOSPITAL: A COHORT STUDY. - Ahmar, Rizwan; Kumar, Manish; Kumar, Amit; Parween, Sadia; Kishore, Sunil; Gupta, Anand Kumar (Student’s Journal of Health Research Africa, 2025)
Background Fetal growth restriction (FGR) is a significant perinatal concern associated with increased neonatal morbidity and long-term pediatric complications. Maternal high-risk factors such as hypertension, diabetes, malnutrition, and infections are known contributors to FGR. Objectives - To clarify the relationship between maternal high-risk variables and the pediatric effects of FGR. - To evaluate the pediatric outcome after 1-year follow-up. Methods A prospective observational study was conducted at IGIMS, Patna, over 1.5 years involving 92 FGR neonates. Maternal risk factors and neonatal outcomes were recorded, with follow-up assessments up to 12 months to evaluate growth and development. Results A total of 92 neonates with fetal growth restriction (FGR) born to high-risk mothers were enrolled. The mean maternal age was 28.4 ± 4.7 years; 48.9% were primiparous. Hypertensive disorders (52.2%) and diabetes mellitus (19.6%) were the most common maternal risk factors. Neonatal outcomes included hypoglycemia (37.0%), respiratory distress (31.5%), and NICU admission (55.4%). Significant correlations were found between maternal hypertension and NICU admission (p=0.003), and between diabetes and neonatal hypoglycemia (p=0.001). At 12-month follow-up, 29.3% had delayed developmental milestones, and 33.7% showed persistent growth impairment, indicating a strong association between maternal risks and adverse pediatric outcomes. Conclusion Maternal high-risk conditions significantly affect both immediate and long-term outcomes in FGR neonates. Early antenatal intervention and structured pediatric follow-up are essential to improve prognosis.